Hepatitis E Vaccine: Present and Future - Rashid, MH; Alim, MA; Rahman, MK; Chowdhary, MM Hoque; Khan, MM Rahman; Mahmood, I; Ekram, ARMS (TAJ: Journal of Teachers Association, 2009)
Viral hepatitis is a major public health problem in the world, and it can be caused by blood- and food-borne viruses. Blood-borne 'hepatitis agents are HBV, HCV and HDV, whereas HAV and HEV are food-borne hepatitis viruses. HEV infection is an important infectious agent in developing countries, but it is also an emerging disease in developed countries, which is likely due to travel or immigration from endemic areas. The main route of human HEV transmission is fecal-oral (fecally contaminated water), although other routes were also reported such as person-to-person transmission, blood products, mother-to-child transmission and zoonotic transmission (e.g., by pigs, particularly in developed countries, and seafood. Epidemiologically, only one serotype of HEV exists in the world, Genetically , the virus has been classified into four genotypes and several subgenotypes designated 1 (1a-e), 2 (2a and b), 3 (3aj) and 4 (4a-g). Each genotype shows a distinct geographical distrib ution. Genotype 1 of HEV is reported from developing countries in Asia and Africa; genotype 2 has been detected in some countries in Africa as well as in Mexico; genotype 3 is distributed globally and genotype 4 of HEV is only found in Asian countries. The genotypes may not only vary with respect to their geographical distribution, but also in their pathogenicity. Genotypes 1 and 2 are primarily human pathogens, causing acute hepatitis in young, nonimmunocompromised people; genotypes 3 and 4, however, have been found in swine and other animals and could therefore be responsible for zoonotic transmissions, preferentially in the elderly or in immunocompromised patients. TAJ 2009; 22(1): 330-336